Drying kinetics and mass transfer properties in the drying of thistle flower - Guiné, Raquel (2019)
Thistle flowers, and particularly their stigmas, are used to coagulate milk in the production of a number of traditional Portuguese cheeses due to their high milk-clotting activity provided by the high content of aspartic proteases. The aim of the present work was to determine the mass transfer properties of thistle ﬂower under different drying conditions: natural drying and convective drying. Convective drying took place in a convection chamber set at different temperatures (35 to 65 °C) and the process was terminated when the sample presented a moisture content of about 5% or less. The traditional drying method was also used, placing the thistle flowers in a dry place sheltered from the sun, and leaving them to dehydrate at the variable room temperature. The present work allowed for the conclusion that convective drying was much faster than natural drying, and that the drying rate increased with temperature. The drying curve revealed an initial constant rate period followed by a falling rate. All the five thin layer models tested to fit the experimental data were shown to adequately describe the drying of the thistle flowers, but the best one was the Page model. The drying constant increased with temperature as did the effective diffusivity and the mass transfer coefficient. The results allowed one to estimate the activation energy for moisture diffusion (57 kJ/mol) and for convective mass transfer (78 kJ/mol). Thus this study showed the possibilities for designing efficient drying processes for the thistle flower used for milk-clotting in the manufacture of traditional cheeses.